Kerangka Kerja Hibryd LCSA–SD: Studi Pendahuluan Pada Industri Manufaktur - Ghaida Fatcha Mubiena (Jurnal Konstruksi, 2025)
The manufacturing industry faces persistent sustainability challenges across environmental, economic, and social dimensions. Life Cycle Sustainability Assessment (LCSA) provides a structured framework for assessing these impacts, but is limited in capturing long-term feedback and dynamics. Meanwhile, System Dynamics (SD) is capable of modeling complex interactions and simulating future scenarios. However, the integration of SD with LCSA remains scarce. This article proposes a hybrid conceptual framework that combines LCSA and SD for sustainability assessment in the manufacturing industry. This framework is based on a literature review and strengthened by an initial conceptual analysis. This approach is expected to produce a more holistic analysis of sustainability trade-offs and serve as a foundation for empirical research, policy evaluation, and strategic decision-making toward more sustainable manufacturing practices.